ニホン ナンキョク チイキ カンソクタイ ニ オケル エットウ キカン チュウ ノ レキダイ ショウビョウ トウケイ : 4233 レイ ノ ケントウ - 大野, 義一朗; オオノ, ギイチロウ; 宮田, 敬博; ミヤタ, タカヒロ; Ohno, Giichiro; Miyata, Takahiro (2000)
P(論文) 日本南極地域観測隊の越冬中の傷病について統計解析を行った。対象は1956年-1999年の歴代越冬隊(昭和, みずほ, あすか, ドームふじの4基地)で越冬報告をもとに集計した。のべ隊員1110名(女性2名), 出発時年齢は22-56(平均33)歳であった。傷病総数は4233件で, 1人あたり傷病数は3.8件であった。科別割合では外科整形外科疾患45.3%, 内科22.7%, 歯科12.7%, 皮膚科7.2%, 眼科5.9%, 耳鼻科3.8%などであった。死亡例はブリザードによる遭難死1例, 全身麻酔手術は行われたことはなく, 1966年腰椎麻酔で虫垂炎手術が1件行われた。感染症が極夜期に増加するなど疾患によっては特有な季節変動を認めた。第39次隊では39名中38名に何らかの傷病が発生し, 総数199件, 1人平均5.1件であった。観測部門と設営部門の間に差はなく, 年齢別では40歳代で最少, 50歳代で最多であった。傷病の31.7%は環境に起因し, 27.6%は仕事が関与していた。 An epidemiological survey of the wintering team personnel of the Japanese Antarctic Research Expedition (JARE) was carried out based on the annual reports of JARE for the period 1956-1999. The total was 4233 illnesses and injuries, an overall rate of 3.8 cases per member during wintering of 12 months. The summary indicates that 45.3% of the cases were surgical and orthopedic cases, 22.7% were internal medical cases and 12.7% were dental problems. One death from a blizzard was recorded. There is no case of a general anesthetic operation, but one appendectomy was done under spinal anesthesia in 1966. From monthly records of diseases, an increase of infectious diseases during the polar night was observed, which suggests a correlation between individual sickness and season of the year. Analysis of JARE-39 wintering members indicated 199 cases affecting 38 of the 39 members, for a rate of 5.1 diseases per person. The incidence in different age groups, showed the lowest rate for the age group of 40-49 and the highest for 50 and over. Of these cases, 31.7% were related to climate and 27.6% were related to work. departmental bulletin paper